Exploring the Roles of HERC2 and the NEDD4L HECT E3 Ubiquitin Ligase Subfamily in p53 Signaling and the DNA Damage Response - Mathieu, Nicholas A.; Levin, Rafael H.; Spratt, Donald E. (Frontiers in Oncology, 2021)
Cellular homeostasis is governed by the precise expression of genes that control the translation, localization, and termination of proteins. Oftentimes, environmental and biological factors can introduce mutations into the genetic framework of cells during their growth and division, and these genetic abnormalities can result in malignant transformations caused by protein malfunction. For example, p53 is a prominent tumor suppressor protein that is capable of undergoing more than 300 post translational modifications (PTMs) and is involved with controlling apoptotic signaling, transcription, and the DNA damage response (DDR). In this review, we focus on the molecular mechanisms and interactions that occur between p53, the HECT E3 ubiquitin ligases WWP1, SMURF1, HECW1 and HERC2, and other oncogenic proteins in the cell to explore how irregular HECT-p53 interactions can induce tumorigenesis.